La Inversión Extranjera Directa y su Incidencia en el Crecimiento Económico - ANDRADE LÓPEZ, JOSÉ (2000)
The purpose of this research is to examine the role of capital flows to emerging economies, in the form of foreign direct investment, through a process of technological diffusion. The analysis uses a theoretical model that starts from a production function of the Cobb Douglas type, in which technological progress is identified as the increase in the number of varieties of inputs or intermediate goods. Technological diffusion from developed economies accelerates the economic growth of these nations. The contribution of this work to the theory of endogenous economic growth lies in the development of the theoretical model presented here. In this model, it is possible, through specific assumptions, to identify the role played by the quality of human capital in the developing economy, by favoring an environment more conducive to receiving foreign direct investment.